The child cases : how America's religious exemption laws harm children - Rogers, Alan, 1936- (University of Massachusetts Press, 2014)
Publisher's description: When a four-year-old California girl died on March 9, 1984, the state charged her mother with involuntary manslaughter because she failed to provide her daughter with medical care, choosing instead to rely on spiritual healing. During the next few years, a half dozen other children of Christian Science parents died under similar circumstances. The children's deaths and the parents' trials drew national attention, highlighting a deeply rooted, legal/political struggle to define religious freedom. Through close analysis of seven cases, legal historian Alan Rogers explores the conflict between religious principles and secular laws that seek to protect children from abuse and neglect.